Implementação de um sistema de eletrodos microfabricados para registro e estimulação neural extracelular in vitro - Vidor, Carolina de Barros (2014)
The main goal of this work was to implement a microfabricated electrode system for in vitro neural stimulation and recording. The MEA biosensor structural characterization was obtained by optical and scanning electrical microscopy images. Qualitative analysis of the chemical composition was made through energy-dispersive X-ray spectroscopy. Analysis of the noise level was conducted by evaluating the RMS value of the potentials recorded with sensors filled with standard saline solution. An electronic interface between a MEA and a conventional data acquisition system with eight channels was constructed and performance tests of the built interface were conducted. Installation of a MEA commercial system was carried out and preliminary tests were performed by experimenting with rodent neuronal cell culture and brain slices. An attempt was made to adapt a conventional perfusion system by peristaltic pump to the MEA system; however, the results were unsatisfactory due to the high noise level of the recordings. Experimental procedures related to the proper handling of MEAs were defined, and the influence of different parameters involved in experimentation with MEAs was investigated. Finally, the data analysis of cell culture recordings indicated detection of local field potentials (LFPs) of greater amplitude, higher counts of spikes and higher spike frequency in the records obtained with standard culture medium compared to those obtained with extracellular electrophysiological solution. The data analysis of cortical slices recordings indicated the detection of a greater number of spikes per minute, higher spike frequency and greater peak-to-peak spikes amplitudes by the microelectrodes that have captured LFPs of greater magnitude.